2018
DOI: 10.3390/nano8070509
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Coated Tin Oxide Nanofibers for Improved Selective Acetone Sensing

Abstract: Three-dimensional hierarchical SnO2/ZnO hetero-nanofibers were fabricated by the electrospinning method followed with a low-temperature water bath treatment. These hierarchical hollow SnO2 nanofibers were assembled by the SnO2 nanoparticles through the electrospinning process and then the ZnO nanorods were grown vertically on the surface of SnO2 nanoparticles, forming the 3D nanostructure. The synthesized hollow SnO2/ZnO heterojunctions nanofibers were further employed to be a gas-sensing material for detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Nevertheless, also in this case, the operating temperature with the highest response is 350 • C [26]. Moreover, Kim et al [34] reported exceptional toluene sensing properties of novel SnO 2 /ZnO core-shell nanowires, functionalized with Pt nanoparticles, showing an excellent R air /R analyte intensity response to 100 ppb at 300 • C. Remarkably, as sticks out, the majority of the most promising reported sensor materials achieve the best performances only at high operating temperatures, especially above 250-300 • C [26,34].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Nevertheless, also in this case, the operating temperature with the highest response is 350 • C [26]. Moreover, Kim et al [34] reported exceptional toluene sensing properties of novel SnO 2 /ZnO core-shell nanowires, functionalized with Pt nanoparticles, showing an excellent R air /R analyte intensity response to 100 ppb at 300 • C. Remarkably, as sticks out, the majority of the most promising reported sensor materials achieve the best performances only at high operating temperatures, especially above 250-300 • C [26,34].…”
Section: Introductionmentioning
confidence: 78%
“…For instance, small polar molecules are better detected than volatile hydrocarbons, and similar VOCs still give identical responses [21,22]. However, the latter issue can be partially solved by adopting different approaches, such as (i) the synthesis of 3-dimensional hierarchical, mesoporous or hollow networks with enhanced surface activity [23][24][25]; (ii) the engineering of nano-heterojunctions that prompt significant changes in the potential barrier height upon exposure to different analytes [26][27][28]; (iii) the doping or decoration with noble metal nanoparticles having a diverse catalytic effect towards a specific VOC molecule; and (iv) the statistical elaboration of data obtained by multiple sensor arrays [29,30]. Hence, in this context, scientific research is focusing attention on the preparation of novel materials able to sense VOCs at room temperature, thus reducing the energy consumption, reaching high sensitivity (of ppb concentration) and a good selectivity [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SnO 2 /ZnO heterojunction nanofibers were prepared following a two-step process (Mailhiot and Duke, 1986;Du et al, 2018). Firstly, the SnO 2 nanofibers were synthesized by the high-voltage electrospinning method.…”
Section: Materials Preparation and Characterizationmentioning
confidence: 99%